MEMBERDAYAKAN HIGHT ORDER THINKING SKILLS (HOTS) MELAUI MODEL DISCOVERY BASED UNITY of SCIENCES (DBUS) - Khasanah, Nur (Phenomenon : Jurnal Pendidikan MIPA, 2018)
The purpose of the research is to know the implementation of Discovery Based Unity of Sciences model in learning biology. The subjects of the study are students majoring in biology education of UIN Walisongo Semarang at first year 2017/2018. Research method using Research and Development (RnD).  Implementation of DBUS model there were 6 steps, ei: (1) Stimulation using local wisdom, (2) Problem statement, (3) Observation and Data collection, (4) Data Processing, (5) Verification base on religion (6) Implementation and awarenest. The N-gain value at UIN Walisongo obtained by the experimental class was 0.23 greater than the control group of 0.09. The results of statistical testing at the UIN Walisongo Semarang obtained the average value of the pretest was 2.45 and the average posttest score was 7.4167. The correlation between pretest posttest was 0.035 <5% with a t value = 9.332 with a sig value of 0.000 <0.05. The T test on the DBUS model at UIN Walisongo from the correlation results on T count is 0.862, showing the results of the correlation on the influence of DBUS model on the increase in PRB is High. The size effect of the DBUS model is categorized as having a large effect because it has a value of d> 0.8 that is d = 0.93.